anonymous
  • anonymous
solve for x: (4x-3)^2=-15
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
so (4x-3)^2=(4x-3)(4x-3) right
anonymous
  • anonymous
yes
anonymous
  • anonymous
so take that and foil it

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Hero
  • Hero
(4x-3)(4x-3) = 4x(4x - 3) - 3(4x - 3) = 16x^2 - 12x - 12x +9 = 16x^2 - 24x + 9
anonymous
  • anonymous
16x^2-24x+24=0
anonymous
  • anonymous
but its not = to 0 its =-15
Hero
  • Hero
(4x-3)(4x-3) = 4x(4x - 3) - 3(4x - 3) = 16x^2 - 12x - 12x +9 = 16x^2 - 24x + 9
anonymous
  • anonymous
my bad see you already did that
anonymous
  • anonymous
so now is there a common number that they are all divisible by?
anonymous
  • anonymous
wait im at 16x^2-24x+9=-15 right?
anonymous
  • anonymous
ya then add the 15 to get 16x^2-24x+24=0
anonymous
  • anonymous
okay yeah i did that
anonymous
  • anonymous
now find a common denominator
anonymous
  • anonymous
8?
anonymous
  • anonymous
yup
anonymous
  • anonymous
so does that then turn into 2x^2-3x=3=0?
anonymous
  • anonymous
2x^2-3x+3 sorry
Hero
  • Hero
16x^2-24x+9=-15 16x^2 - 24x + 24 = 0 8(2x^2 - 3x + 3) = 0 2x^2 - 3x + 3 = 0 x^2 - 3/2 + 3/2 = 0 x^2 - 3/2x = -3/2 x^2 -3/2x + 9/16 = -3/2 + 9/16 (x - 3/4)^2 = -15/16 Solution is imaginary
anonymous
  • anonymous
yes
anonymous
  • anonymous
then what do i do?
anonymous
  • anonymous
the answer is 3 + or - the square root of 15 divided by4 but idk how to get it
anonymous
  • anonymous
i would do the quadratic formula
anonymous
  • anonymous
-b + or - the square root of b^2 -4ac divided by 2a?
Hero
  • Hero
\[\frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\]
anonymous
  • anonymous
(-b+-sqrt(b^2-4ac))/2a
anonymous
  • anonymous
yup
anonymous
  • anonymous
i got it thanks to both of you!
anonymous
  • anonymous
not a problem
Hero
  • Hero
You got what? Mind sharing what you got?
anonymous
  • anonymous
3 + or - the square root of 15 divided by 4
anonymous
  • anonymous
3+ or - i square root 15 divided by 4 sorry i forgot the "i"
anonymous
  • anonymous
yup

Looking for something else?

Not the answer you are looking for? Search for more explanations.